Videogames for academic wellbeing: a biopsychosocial health psychology framework for university counseling and mental health promotion - Eugenio De Gregorio; Ilaria De Laurentiis (Frontiers in Psychology, 2026)
In recent years, videogames have attracted growing attention not only for their recreational value, but also for their potential to foster personal and social identity, enhance cognitive functioning, and promote psychological wellbeing. Consistent with a biopsychosocial perspective on health, this paper conceptualizes gaming as a psychological, behavioral, and social resource that can be purposefully integrated into health-promotion practice, and explores its use within care contexts, with a particular focus on university students. In 2025, Link Campus University in Rome launched a psychological support service funded by the Wave Pro-ben project (Project ID: PROBEN_0000007), supported by the Italian Ministry of University. The service targets students enrolled in degree programmes, PhDs, and master's courses, addressing emotional, relational, academic, and adaptation-related challenges. Counseling initiatives promote psychological wellbeing, prevent distress, and foster personal growth, thereby reducing dropout risk and supporting academic success. Activities include individual sessions, support groups, workshops, and psychoeducational interventions, offered confidentially and free of charge—a design choice intended to reduce barriers of access and stigma. The distinctive element of the service is the integration of videogames as tools for reflection and change. Traditional counseling has been complemented by structured gameplay, drawing on Video Game Therapy ® (VGT), developed by Francesco Bocci. VGT ® is conceptually intended to create opportunities for emotional recognition and regulation, cognitive engagement, agency, and social-skill development; however, evidence specifically evaluating VGT ® remains preliminary. Research shows that, while excessive gaming carries risks—such as isolation, anxiety, and problematic use—balanced and intentional play can provide meaningful benefits, stimulating flow states in which individuals process emotions, revisit past experiences, and develop adaptive coping strategies. By integrating games into counseling, the approach also engages students who may avoid traditional support due to stigma or skepticism, thus contributing to more equitable access to psychological care in higher education. As a conceptual and programmatic Community Case Study, the paper does not present effectiveness data. Instead, it describes the theoretical rationale, institutional context and key operational elements of the model, distinguishes the broader evidence on videogaming and wellbeing from the still preliminary evidence specific to VGT ® , and outlines a framework for prospective empirical evaluation.